Availability, prices and affordability of selected essential medicines in Jordan: a national survey - Qais Alefan; Rawan Amairi; Shoroq Tawalbeh (BMC Health Services Research, 2018)
Abstract Background Free access to essential medicines is a fundamental right. Governments should provide accessible and affordable medicines to people. The purpose of this study was to evaluate medicines’ prices, availability and affordability in Jordan. Method Data was collected from 30 public sectors and 30 private sectors in 6 regions in Jordan. At each institution, the availability and prices data of 50 originator brand (OB) medicines and lowest-price generic (LPG) equivalent medicines were collected. Medicines’ prices were compared with international reference prices (IRPs) to obtain a median price ratio (MPR). Availability of medicines was determined on the day of data collection. Affordability was calculated with regards to the daily income of the lowest-paid unskilled government employee. Result Availability of medicines in public and private sectors was 72% and 76% for LPGs, respectively. Median MPRs of procurement prices for OBs and LPGs in the public sector were 1.1 and 5.5 times the IRPs, respectively. Private sector OB medicines were priced 4.8 times higher than IRPs, whereas LPGs were 3.8 times higher. OBs cost 14% more than LPGs in private sector. The median MPRs of patient prices for LPGs in the public sector were lower than in the private sector (1.1 versus 7.6). Generally, medicines’ prices are affordable in public sector that the lowest paid unskilled government employee need less than a 1 day income to purchase the LPGs. While in private sector, the medicine prices are not affordable. For example, the treatment of hypertension either by LPGs or OBs needs more than 1 day income by lowest paid unskilled government employee. Conclusion This study showed good availability of LPGs in the public sector. In private sector, it showed good availability of LPGs and OBs with higher patient prices. The procurement prices in the public sector were reasonable in comparison to IRPs. Policy evaluation efforts must be directed to cut medicines prices and to improve affordability in private sector.